Enhancement of Radiosensitization by Silver Nanoparticles Functionalized with Polyethylene Glycol and Aptamer As1411 for Glioma Irradiation Therapy - Zhao J (Dove Medical Press, 2019)
Jing Zhao,1 Peidang Liu,1,2 Jun Ma,3 Dongdong Li,1 Huiquan Yang,1 Wenbin Chen,1 Yaowen Jiang2 1School of Medicine, Southeast University, Nanjing 210009, People’s Republic of China; 2Jiangsu Key Laboratory for Biomaterials and Devices, Southeast University, Nanjing 210096, People’s Republic of China; 3Radiotherapy Department, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing 210029, People’s Republic of ChinaCorrespondence: Peidang LiuSchool of Medicine, Southeast University, 87 Dingjiaqiao Road, Nanjing 210009, Jiangsu Province, People’s Republic of ChinaTel/Fax +86 25 8327 2554Email seulpd@163.comBackground: The efficacy of radiotherapy for glioma is often limited by the radioresistance of glioma cells. The radiosensitizing effects of silver nanoparticles (AgNPs) on glioma were found in the previous studies of our group. In order to enhance the radiosensitivity of tumor cells and selectively kill them while reducing the side effects of irradiation therapy, targeted modification of AgNPs is urgently needed.Materials and methods: In the present study, AgNPs functionalized with polyethylene glycol (PEG) and aptamer As1411 (AsNPs) were synthesized and subsequently characterized by transmission electron microscopy, ultraviolet-visible spectroscopy and Fourier transform infrared spectroscopy. Then the targeting property of AsNPs was evaluated by dark-field imaging, confocal microscopy and in vivo imaging. Both colony formation assay and glioma-bearing mouse model were employed to study the radiosensitizing effect of AsNPs.Results: The characterization results revealed a spherical shape of AgNPs with an average diameter of 18 nm and the successful construction of AsNPs. AsNPs were confirmed to specifically target C6 glioma cells, but not normal human microvascular endothelial cells. Moreover, AsNPs could not only internalize into tumor cells, but also penetrate into the core of tumor spheroids. In vitro experiments showed that AsNPs exhibited a better radiosensitizing effect than AgNPs and PEGylated AgNPs (PNPs), inducing a higher rate of apoptotic cell death. In vivo imaging demonstrated that Cy5-AsNPs preferentially accumulated at the tumor site, and the ratio of fluorescence intensity of Cy5-AsNPs to that of Cy5-PNPs reached the maximum at 6 h post-systemic administration. Furthermore, the combination of AsNPs with irradiation significantly prolonged the median survival time of C6 glioma-bearing mice.Conclusion: Our results indicated that AsNPs could be an effective nano-radiosensitizer for glioma targeting treatment.Keywords: radiosensitization, As1411, silver nanoparticles, glioma